Is Load Application Necessary When Using CT Scans to Diagnose Syndesmotic Injuries? A Cadaver Study. Issue 4 (16th October 2019) - Barg, Alexej; Weinberg, Maxwell W.; Davidson, Nathan P.; Hintermann, Beat; Saltzman, Charles L.; Krähenbühl, Nicola
Category: Ankle, Trauma, Imaging Introduction/Purpose: Injury to the distal tibio-fibular syndesmosis is common and appears in up to 20% of patients with an ankle sprain or ankle fracture. While pronounced injuries can be reliably diagnosed using conventional radiographs, assessment of subtle syndesmotic injuries is challenging. With the introduction of weightbearing CT (WBCT) scans, detailed assessment of foot and ankle disorders under load bearing conditions became possible. The purpose of this cadaver study was to assess the influence of weight on assessment of incomplete and more complete syndesmotic injuries using two-dimensional (2D) measurements on axial CT images. We hypothesized that weight would significantly impact assessment of both incomplete and more complete injuries to the distal tibio-fibular syndesmosis. Methods: Fourteen paired male cadavers (tibial plateau to toe-tip) were included. A radiolucent frame held specimens in a plantigrade position while both non-weightbearing and weightbearing CT scans were taken. Four conditions were tested: First, intact ankles (Native) were scanned. Second, one specimen from each pair underwent anterior inferior tibio-fibular ligament (AITFL) transection (Condition 1A), while the contralateral underwent deltoid transection (Condition 1B). Third, the remaining intact deltoid or AITFL was transected (Condition 2). Finally, the distal tibio-fibular interosseous membrane (IOM) was transected in all ankles (Condition 3). For each condition, non-weightbearing, half-bodyweight (42.5 kg), and full-bodyweight (85 kg) CT scans were taken. Six measurements were performed to assess the integrity of the distal tibio-fibular syndesmosis on axial CT scans 1 cm above the ankle joint (Figure 1A/ B) and two measurements at the level of the talar surface (Figure 1C). Inter- and intra- observer agreement were additionally calculated. Results: Inter- and intra-observer agreement differed between measurements. Excellent agreement was evident for the tibio- fibular clear space (TFCS) and tibio-fibular overlap (TFO) with an intra-observer agreement of 0.79 and 0.94, respectively. Poor agreement was evident for Angle 1 (inter-observer, 0.39). Agreement of the other measurements (inter- and intra-observer) was either rated as fair or good and ranged from 0.44 to 0.71. Weightbearing had no significant influence on measurements. Only more complete injuries (Condition 3) differed from native ankles when using either the anterior tibio-fibular distance (ATFD) or TFO. For these two measurements, no significant differences were observed within each condition between non-, half-, and full- weightbearing. Also, no significant differences were evident between single AITFL and deltoid ligament transection for the ATFD and TFO. Conclusion: Load application does not impact the ability of WBCT scans to diagnose incomplete and also more complete syndesmotic injuries in a cadaver model. The utility of current 2D measurements on axial WBCT scans for diagnosing incomplete syndesmotic injuries is questionable. Nevertheless, the ability to reliably position the foot during imaging is an advantage of WBCT technology over other imaging options. Further investigations using more precise measurement options (e.g. 3-dimensional [3D] measurements) are necessary to better understand the potential role of weight bearing to diagnose syndesmotic injuries with CT scan imaging technology.